DETECTION OF CACHE-BASED SIDE CHANNEL ATTACK IN PRIVATE CLOUD COMPUTING USING BLOOM FILTER - MUNISH, CHOUHAN (2017)
Cloud computing empowers various different users to share configurable computing resources. Resource sharing benefits users in lowering their financial burden, therefore, helps in boosting start-ups with rational capital. However, resource sharing raises the risk of a breach in data security and privacy. In cloud computing, multiple virtual machines (VM) share common underlying infrastructure, like network, memory units, etc. Multiple VMs sharing the same cache in cloud computing are creating opportunities for the Cache-based Side Channel Attack (CSCA).